Um estudo exploratório sobre a relação entre a estrutura de capital e o retorno das ações das empresas brasileiras nas financeiras no período de 1995 a 2004. - Velloni, Ana Carolina (2006)
The main objective of this work is to analyze the potential relationship between stock return and the capital structure adopted by Brazilian Companies. Specifically, this dissertation analyzes the hypothesis that the stock return of leveraged companies is not equivalent to the stock return obtained from unleveraged companies, in average. The analysis considered non-financials Brazilian Companies, with stocks negotiated at the Brazilian Stock Exchange - BOVESPA, from 1995 to 2004. Hypothesis testing of the mean value of the studied populations was used, observing the calculation of the average significance for two samples, analyzing the market value of the debt and the abnormal stock return comprising the extra gain per share when compared to the IBOVESPA, in this case the market parameter. Thus, two portfolios were created: one composed of highly leveraged company stocks and the other composed by the lowest leveraged company stocks. Each portfolio comprises the quintile of most and least leveraged stocks. The results show evidences that the average return for the portfolios is different, illustrating that portfolios composed by stocks of companies with different capital structure provide, in average, different abnormal returns. In this case, the portfolio composed by high leveraged stocks presented abnormal return higher than the portfolio composed by unleveraged stocks. For the analyzed period, 10 years, the abnormal return for leverage portfolio was, in average, 18% higher than the return for unleveraged stocks. In order to confirm the results, confirmation tests were provided, considering: total debt at book value for the whole period, total debt at market value for 5 years and for 1 year. This work corroborates the results obtained from other researchers, especially in more mature capital markets, such as England and Australia